2015
DOI: 10.1111/medu.12653
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the impact of high- and low-fidelity instruction in the development of auscultation skills

Abstract: The results from this study suggest that highly contextualised learning environments may not be uniformly advantageous for instruction and may lead to ineffective learning by increasing extraneous cognitive load in novice learners.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
1
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(45 citation statements)
references
References 36 publications
1
41
1
2
Order By: Relevance
“…Several investigators have demonstrated that simulation-based medical education is effective in cardiac auscultation [12,14,15,17,19]. In contrast, others reported no significant differences in the proficiency in cardiac auscultation between learners trained by high-fidelity simulation and those trained by low-fidelity simulation or no intervention [13,16,18,20]. In our present study, the accuracy rates in identifying heart murmurs were 81.3% in the first test and 77.5% in the second test.…”
Section: Discussioncontrasting
confidence: 78%
See 1 more Smart Citation
“…Several investigators have demonstrated that simulation-based medical education is effective in cardiac auscultation [12,14,15,17,19]. In contrast, others reported no significant differences in the proficiency in cardiac auscultation between learners trained by high-fidelity simulation and those trained by low-fidelity simulation or no intervention [13,16,18,20]. In our present study, the accuracy rates in identifying heart murmurs were 81.3% in the first test and 77.5% in the second test.…”
Section: Discussioncontrasting
confidence: 78%
“…Although technology-enhanced medical simulation is a useful tool for health professional learners to acquire a variety of knowledge and skills as well as desirable behaviors [11], its effectiveness in cardiac auscultation training is still controversial [12][13][14][15][16][17][18][19][20]. Furthermore, it is not known whether the effectiveness of auscultation training using a cardiology patient simulator differs among a variety of heart sounds and murmurs.…”
Section: Introductionmentioning
confidence: 95%
“…According to Hamstra et al ,10 classifying fidelity as either high or low is too simplistic. Converse arguments suggest that increased authenticity is typically accompanied by greater complexity, which may reduce learning and variability in the presentation of a particular condition 11. That being said, simple task trainers are not without consequence limited capability can provide ‘negative training’.…”
Section: Discussionmentioning
confidence: 99%
“…Given that many professional issues arise during clinical placement for which the virtual patient cases might provide an excellent resource, this is problematic. The virtual patient cases themselves must be free of non-working links or other technological glitches which impede student experience and could add to their cognitive load (Chen et al, 2015). Support in terms of readily accessible "help lines" (for students and faculty) is important to optimize learning experience.…”
Section: Tip #10: Provide Adequate Technical Supportmentioning
confidence: 99%
“…Overly complex cases add additional cognitive load to novice learners which may inhibit learning (Chen et al, 2015;Cook & Triola, 2009), while overly simple cases are not engaging for more advanced learners (Geishundheit et al, 2009). Cases early in the curriculum may focus on knowledge acquisition, such as the content of codes of ethics, while later cases may focus on ethical decision making in situations which present a challenge to the Murphy S, Imam B, Whitehouse L MedEdPublish https://doi.org/10.15694/mep.2016.000107 Page | 4 learnersevolving professional identity.…”
Section: Tip #5: Watch For the Informal Curriculummentioning
confidence: 99%